The Role of Technology in Indonesian Education at Present - Salma Rabani; Annisaul Khairat; Xie Guilin; Deng Jiao (Yayasan Adra Karima Hubbi, 2023)
Technology has become increasingly important in education, including in Indonesia. The implementation of technology in education is expected to improve the quality of education and help reduce the gap in education access across regions. However, several factors have hindered the implementation of technology in education in Indonesia, such as limited infrastructure, inadequate training and development for teachers and lecturers, and digital divides between regions. Despite these challenges, the use of technology in education has several benefits, including improving the quality of learning and motivation of students and increasing the efficiency of administrative tasks for teachers and lecturers. To improve the implementation of technology in education in Indonesia, efforts are needed to develop supporting infrastructure, provide training and development for educators, and establish clear policies and regulations. Collaboration between the government, educational institutions, and the private sector is also necessary. This article discusses the role of technology in education in Indonesia and the factors that influence its implementation, drawing on various studies and research.